ARQUITETURAS DA NOTÍCIA EM DISPOSITIVOS MÓVEIS: ANÁLISE DE APLICATIVOS JORNALÍSTICOS BRASILEIROS E PORTUGUESES PARA SMARTPHONES - NISHIYAMA, ALEXANDRA FANTE (2017)
The history of journalism is linked to technology. Smartphones connected to broadband internet and apps have created a mobile environment, favorable to journalism for mobile devices, with features that change the ways of production, distribution and consumption of content. This environment establishes a closer relationship with the person. The small screens of these devices establish a new way of interaction and the need for changes in journalism such as texts arranged in small blocks, the use of hyperlinks and the customization of apps. From this context, the general objective of this thesis is to investigate trends in the architecture of the news in journalistic apps for mobile devices of Brazilian and Portuguese media companies, identifying patterns according to specific features of the item. By doing so, it is aimed to understand and point out the architectural characteristics of the news in journalism for mobile devices. There is the hypothesis that journalistic contents produced and published in apps have similar architecture, with characteristics close to web journalism, highlighting different levels of use of tools available for smartphone. The research with exploratory and descriptive nature, which covers the qualitative and quantitative methods, adopted the analysis of content a technique of investigation. Two analysis were developed. An objective one analyzes news content and the other evaluates software (journalistic app) and hardware (smartphone). The journalistic apps analyzes are a total of six, the Brazilian – Folha de S. Paulo, Estadão, and O Globo and, the Portuguese – Observador, Público and Expresso. Based on the results achieved it was proved the hypothesis that the news content produced for mobile devices and published in journalistic apps have similar architecture, with characteristics close to web journalism, highlighting different levels of use of available tools for smartphone, though only some possibilities of the device are adopted